Cardioneuroablation in the treatment of neurally mediated reflex syncope: a review of the current literature - Tolga Aksu; Tümer Erdem Güler; Serdar Bozyel; Kazım Serhan Özcan; Kıvanç Yalın; Ferit Onur Mutluer (KARE Publishing, 2017)
Objective: An imbalance between parasympathetic and sympathetic tone is a main cause of neurally mediated reflex syncope (NMRS). These patients may be very symptomatic and the condition may require cardiac pacemaker implantation. Cardioneuroablation (CNA) is a relatively novel technique based on radiofrequency ablation of vagal ganglia that can be used in treatment of NMRS. The aim of this analysis was to compare potential role of CNA in patients with NMRS.  Methods: In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Statement, literature search was conducted using the keywords 'cardioneuroablation,' 'vagal denervation,' 'reflex syncope,' 'vagal ablation,' and 'ganglionic plexi ablation.' Retrieved citations were first screened independently by 2 reviewers for inclusion and exclusion criteria. Results: Freedom from syncope and freedom from prodrome were 100% and between 50% and 100%, respectively, in the studies. Ablation was performed via both atria in 3 studies; only left atrial approach was used in the remaining studies. There was no major complication related to the procedure reported.  Conclusion: Focused or extensive vagal ganglia ablation may be a potential alternative to pacemaker implantation in a carefully selected patient population. In contrast to pharmacological therapy and pacemaker implantation, ganglia ablation is designed to get to the root of the problem: disturbances in the intrinsic cardiac autonomic nervous system. This novel technique should be evaluated in large-scale, randomized, controlled trials.